From Folklore to Conspiracy Beliefs: A Gramscian Approach to Conspiracy Theory Studies - Maria Chiara Pozzoni; Giuseppe Quattromini (Genealogy)
This paper applies Antonio Gramsci’s theory of folklore—defined as the cultural expressions of subaltern groups reflecting their lived experiences of subalternity—to contemporary conspiracy beliefs, arguing that these beliefs function as a form of what he called “modern folklore”. Drawing on Gramsci’s insights into hegemony, it examines how subaltern beliefs emerge as both reflections of and responses to sociocultural conditions. The paper demonstrates that conspiracy mentality, akin to Gramscian folklore, inadequately encapsulates the issues and aspirations of those feeling marginalised and not represented within hegemonic systems. It outlines how distorted elements of modern scientific and political thought are integrated into folklore, resulting in inconsistent and fragmented worldviews. Key topics include the role of commercial literature in shaping subaltern consciousness and the political implications of conspiracy beliefs, particularly how they are utilised by reactionary movements to further their agendas. The analysis concludes with two case studies: one from Gramsci’s writings and another on contemporary conspiracy beliefs related to COVID-19, illustrating how these examples exemplify modern folklore. This approach offers a critical framework for understanding the social, cultural, and political origins and functions of conspiracy beliefs, highlighting the relevance of Gramsci’s thought to conspiracy theory studies.